Talking about Writing – Designing and Establishing Writing Feedback and Tutorials to Promote Student Engagement and Learning - Börjeson, Fia Christina; Carlsson, Carl Johan (Journal of Academic Writing, 2020)
This article describes different feedback designs that have been developed at Chalmers University of Technology, Sweden. These feedback activities are part of courses and programmes that faculty at the Department of Communication and Learning in Science, Division for Language and Communication, are involved in. The feedback setup has evolved from many years of designing and delivering writing instruction within STEM education, grounded in the challenge to make feedback a meaningful learning experience for all students and improve students’ understanding of disciplinary academic writing. The feedback designs described are based on dialogue to provide feedback and as a means for students to verbalize their own understanding of text, textual features and how discipline specific content is communicated. Examples of setups are large class active feedback lectures, scaffolded peer response sessions, and guided feedback workshops. These feedback activities are explored, and we argue for how they, potentially, result in more (useful) feedback and feedforward compared to traditional written teacher-student feedback.